A sucrose repression element in the Phaseolus vulgaris rbcS2 gene promoter resembles elements responsible for sugar stimulation of plant and mammalian genes - Urwin, N.A.R. (Glasgow Univ. (United Kingdom). Inst. of Biomedical and Life Sciences); Jenkins, G.I (Plant molecular biology, 1997)
Protoplasts isolated from the primary leaves of Phaseolus vulgaris L. were used in transient expression experiments to identify promoter sequences of the P. vulgaris rbcS2 gene, encoding ribulose 1,5-bisphosphate carboxylase/oxygenase small subunit, concerned with sucrose repression. The protoplasts supported high rates of expression of the chloramphenicol acetyl transferase reporter gene fused to 1433 bp of the rbcS2 5' flanking sequences. Expression was repressed by 50 mM sucrose whereas that driven by control promoters was not. Assays of promoter deletions revealed that 203 bp 5' to the transcription start site were sufficient for high rates of sucrose-repressible expression. A -187 bp deletion supported much lower rates of expression and was not subject to sucrose repression. The -203 to -187 bp region contains sequences resembling elements involved in the sugar stimulation of transcription of other genes: the SURE (sucrose response element) of plant genes and the ChoRE (carbohydrate response element) of mammalian genes. A G-box (CACGTG) located at -200 to -205 was important for high levels of sucrose-repressible expression, since deletion of a nucleotide from this element in the context of the 1433 bp promoter gave much reduced expression. However, a modified G-box (CcCGTG) in the -203 bp fusion and adjacent vector sequences remained functional. Measurements of rbcS and chalcone synthase (CHS) transcript levels in the protoplasts indicated that 4 mM sucrose was sufficient to repress or stimulate the respective genes. Further experiments suggested that metabolism of 6-carbon sugars is the signal for rbcS repression and CHS stimulation.